1992
DOI: 10.1001/jama.1992.03480060073033
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delirium in Hospitalized Elderly

Abstract: Delirium in hospitalized patients is most closely associated with factors already present on admission such as prior cognitive impairment, advanced age, and fracture. In the hospital, use of neuroleptics and narcotics and the presence of infection are less strongly associated with this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
5
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(201 citation statements)
references
References 26 publications
9
176
5
8
Order By: Relevance
“…Various studies have indicated the multifactorial nature of delirium and have found that between two and six factors may be present in any single case 3031. Next to increasing age, pre-existing cognitive decline is the most confirmed risk factor 32.…”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%
“…Various studies have indicated the multifactorial nature of delirium and have found that between two and six factors may be present in any single case 3031. Next to increasing age, pre-existing cognitive decline is the most confirmed risk factor 32.…”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%
“…23 The risk factors of increasing age and baseline cognitive or functional impairment for development of delirium also reflect the risk in general medical inpatients. 6,22,30,36 Alcohol abuse and marked abnormalities in preoperative sodium, potassium, or glucose levels (which may be a reflection of diuretic use and dehydration) have been reported as predictors of POCD. 23,[37][38][39] Finally, low educational levels have also predicted POCD, 5,34 as subjects with higher levels of education may perform relatively better on tests with a high learned component (e.g., language and secondary memory) than on tests measuring attention, implicit memory, and visual-spatial analysis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…4,23,48 In other studies, opioids other than meperidine and anticholinergic agents have not been associated with delirium. 23,30 Although deliberate hypotension per se does not appear to influ- ence development of POCD, a postoperative hematocrit less than 30% (odds ratio ϭ 1.7) was independently associated with a higher incidence of postoperative delirium in patients older than 50 years undergoing major elective noncardiac surgery. 14 In addition, the presence of postoperative infections and respiratory complications has been shown to significantly correlate with development of POCD.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Most agents in this class affect basic CNS functions and can cause transient periods of dizziness with balance or visual impairment, in addition to confusion and transient memory loss. [28] Patients with impaired hepatic metabolism and impaired renal elimination may be more sensitive to usual recommended adult doses. To prevent fall events associated with urgency, pharmacological factors should be evaluated along with environmental adjustments.…”
Section: Discussionmentioning
confidence: 99%